Pendidikan Kewirausahaan dan Digital Marketing dalam Menghadapi MEA Bagi Para Siswa di Perbatasan Negara - Irwan Iskandar; Pazli; Hendrini Renolafitri; Herliana Rahmi MD; Jihan Nabila Fahmi; Nurhayati (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2023)
Since 2016, citizens in Indonesia have faced free competition within the framework of the AEC (ASEAN Economic Community). For this reason, the first step in facing the AEC is to introduce younger generation, especially at the state's borders, to the opportunities and challenges within the AEC. After that, there must be efforts to cultivate entrepreneurial character along with selling products or services through digital marketing/marketplace. Based on the purpose, this community service activity is carried out by using counseling approach and by targeting students of SMA Negeri 1 Rupat Utara on the edge of the Malacca Strait. After its implementation, it is known that the students, from not knowing the AEC, become aware of the AEC. They are more motivated to face AEC by doing business after finishing school, continuing their education to college or working as a trained workforce. The conclusion of this activity is that the students of SMAN 1 Rupat Utara already have an entrepreneurial character. It's just that these characters must be honed and directed so that they are maximized in facing AEC.